Profitability and efficiency of conduction systems and optimal tomato density for fresh consumption - Dipple, Fernanda Lourenço; Ponce, Franciely da Silva; Toledo , Claudia Aparecida de Lima; da Silva, Rejeane Maria; Grzebieluckas, Cleci; Seabra Júnior, Santino (Comunicata Scientiae, 2024)
This study evaluated the productivity and economic profitability of cultivation systems for the table market. A hybrid tomato cultivar, Fascínio was grown in 12 cultivation systems of the “half stake”, “open V”, and “low” types, with four spacings–0.2, 0.3, 0.4, and 0.5 m between plants and 1.5 m between rows. Eleven fruits were harvested at the mature stage, and the productive (total, commercial, and non-commercial productivity, percentage of losses, and types of damage) and economic (production cost, revenue, and profit) parameters were evaluated. The half-stake and low (both with 0.2 m spacing) cropping systems showed the highest total yields (179 t ha-1), differing from the open V (154.4 t ha-1) and half-stake (0.2 m spacing) systems at higher commercial productivity (158.1 t ha-1). With a production cost below 100 thousand R per hectare and a profitability index above 58%, the half-stake and low (0.2 m spacing) cultivation systems proved to be more productive and economically efficient than the open V system, fulfilling the requirements of tomato growers. The creeping system (0.2 m spacing) had the highest percentage of losses (22%) due to non-marketable fruits; Based on damage nature, the half-stake system tomatoes showed black backgrounds and the open and creeping systems showed tomato locules affected by pests.